Natura e funzioni del linguaggio e del pensiero nella concezione freudiana - Salvador, Luca (Metapsychologica - rivista di psicanalisi freudiana, 2023)
The article presents a description of the functions of language in the way it emerges from the works of Freud, starting from the neuropsychological texts on aphasia up to the metapsychological texts of maturity. It emphasises its importance in liberating thought processes from the pleasure principle and, in general, its importance in controlling psychological events from topical, energetic and dynamic points of view. The language enables a complex perceptive articulation of internal phenomena which are otherwise destined to remain unconscious or only vaguely perceived monotonously as pleasant or unpleasant. Its functions therefore are strictly associated with managing a homeodynamic complex of drives. The language allows in this way, for the cognitive development of thought.